Acanthamoeba GENUS FREE-LIVING AMOEBAE ISOLATED FROM ICA CITY WATER SOURCES - SUÁREZ, ROXANA (2002)
OBJECTIVE: To determine the presence of Acanthamoeba genus in several Ica city (south of Lima) water sources. MATERIAL AND METHODS: Thirty-one samples from 7 natural water sources (lagoons) and 24 artificial sources (wells, tanks for rehabilitation therapy, reservoirs and cisterns) were examined during May 1997 in several points of the city. Samples were sowed in Agar Myast and in Agar Napolitan, incubated at 37°C and checked after 10 days. Positive samples were inoculated to immunocompetent mice by intranasal route; resultant lesions were cultured again following the same procedure. RESULTS: In 11 samples (35,5%) Acanthamoeba cysts were isolated, 6 from natural sources and 5 from artificial sources; among negative samples only one came from natural source and the other 19 came from artificial sources inside homes or from the local hospital. OR =22,8 was obtained for exposition to natural sources of water, as cause of infection (confidence limit 95% 1,83-642,55, X2 =7,83). CONCLUSIONS: Presence of Acanthamoeba genus is more frequent in natural water sources at Ica city. Further studies are necessary to confirm this situation.